Mast cells boost anti-tumor potency of MAIT cells via inflammasome-dependent secretion of IL-18 - Fanfan Fan; Jun Wang; Kun Liu; Shiyue Zhang; Jian Gao; Xiongfei Li; Jiaqiang Ma; Yue Zhao; Teng Li; Han Su; Xinfeng Yang; Han Han; et al. (Nature Communications)
Abstract Mast cells (MC) serve as pivotal sentinels in the regulation of immune responses and inflammation, yet their function in lung adenocarcinoma (LUAD) remains largely neglected. To decode their heterogeneity, we perform single-cell transcriptomic analysis of LUAD-infiltrating MCs. Our study uncovers the complexity in MC composition and identifies 9 distinct states, including proinflammation, chemotaxis, and antigen presentation. The proinflammatory MC subset, characterized by high IL-18 expression, is associated with improved outcomes for LUAD patients. This pro-inflammatory property is regulated by the activation of NLRP3 inflammasome within MCs, resulting in the formation of GSDMD pores and successive pyroptosis. Moreover, these MCs enhance the innate-like anti-tumor activity of MAIT cells by upregulating NKG2D and IFN-γ through the cytokine-activation mechanism. Our results uncover an unappreciated state of MCs and describe an inflammasome-dependent, MC-mediated regulation of MAIT cells in LUAD. These findings diversify our understanding of the functional repertoire and mechanistic equipment of MCs and MAIT cells, and suggest a potential therapeutic target for cancer treatment.